Nurturing Piety: The Interplay of New Media, Youth Muslim and Commodification: (Hanan Attaki’s Sharing Time Study Case) - Asya Dwina Luthfia; Rohmat Yanuri, Yusuf (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study investigates the ways in which the contemporary viral public sermons, Hanan Attaki’s Sharing Time, represented in the contemporary viral public sermons, intertwine the roles of social media, the youth movement, and piety included within the religious commodification. The author also examines how, in this disruptive age, the piety of young people could be addressed with the given religious teachings or da’wah he offers. This research also explores the complex relationship between young Muslim ide in Indonesia, and social media. It can be examined as to how social media platforms and digital technology influence the phenomena of viral public sermons. It observes the shift in Islamic traditions, the emergence of skepticism, and the dynamics of Islam and the modern world especially in the technological world. Religious populism, together with the new authority that has emerged due to the changes in religious expression and participation due to social media have altered the dynamics of religious discourses. This paper pays further attention to the urbanization process, the ‘Pop Islam’ phenomena, and the hijrah movement as a critical development in the emerging forms of Muslim religiosity in contemporary Indonesia. Discussing the relation of identity and piety together, it focuses on the commercialization of religion and the entwinement of tradition and modernity in Islamic popular culture. This essay highlights the fluidity of cultural change in Indonesian Muslims’ youth identity through the Hijrah movement that metaphorically represents change in identity, and furthermore underscores the daily struggle between tradition and modernity within the Indonesian Muslim community.